Autonomic nervous system responses to strength training in top-level weight lifters - Iellamo, F.; Lucini, D.; Volterrani, M.; Casasco, M.; Salvati, A.; Gianfelici, A.; Di Gianfrancesco, A.; Urso, A.; Manzi, V. (Physiological Reports, 2019)
In athletes, spectral analysis of HR variability (HRV) has been shown capable to detect the adaptational changes in sympatho-vagal control attending physical training. So far, studies investigated autonomic nervous system (ANS) changes occurring with endurance training, whereas adaptations to markedly different exercise modes, for example, strength training, have never been investigated. We assessed the changes in cardiac ANS parameters during long-term training in weight lifters of the Italian team preparing for the European Championship, where athletes competed for obtaining the pass for Olympic Games. We investigated nine athletes. Subject trained 3 sessions/day, 6 days a week. The intensity of strength exercises varied from 70% to 95% 1 RM. Training load (TL) was calculated as: volume (min) × intensity (%1RM).All ANS parameters were significantly and highly correlated on an individual basis to the dose of exercise with a second-order regression model (r2 ranged from 0.96 to 0.99; P < 0.001). The low-frequency (LF) component of HRV and LF/HF ratio showed an initial increase with the progression of TL and then a decrease, resembling a bell-shaped curve with a minimum at the highest TL. The high-frequency (HF) component of HRV and R-R interval showed a reciprocal pattern, with an initial decrease with progression of TL followed by an increase, resembling an U-shaped curve with a maximum at the highest TL. These adaptations were at the opposite to those previously reported in endurance athletes. These results suggest that in Olympic weight lifters, ANS adaptations to training are dose-related on individual basis and that ANS adaptations are mainly sport-specific.